2007
DOI: 10.1590/s1415-47572007000600014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of Cuban traditional rice (Oryza sativa L.) varieties based on microsatellite markers

Abstract: Microsatellite polymorphism was studied in a sample of 39 traditional rice (Oryza sativa L.) varieties and 11 improved varieties widely planted in Cuba. The study was aimed at assessing the extent of genetic variation in traditional and improved varieties and to establish their genetic relationship for breeding purposes. Heterozygosity was analyzed at each microsatellite loci and for each genotype using 10 microsatellite primer pairs. Between varieties genetic relationship was estimated. The number of alleles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
(37 reference statements)
0
18
0
1
Order By: Relevance
“…A similar criterion was followed by Alvarez et al, (2007). In this study, 26 frequent alleles were identified among 139 loci, with an average of 0.19 alleles per locus.…”
Section: Frequent Rare and Unique Allelesmentioning
confidence: 71%
“…A similar criterion was followed by Alvarez et al, (2007). In this study, 26 frequent alleles were identified among 139 loci, with an average of 0.19 alleles per locus.…”
Section: Frequent Rare and Unique Allelesmentioning
confidence: 71%
“…Very frequent alleles were considered to be those occurring in more than 10% of the varieties in the collection, whereas those occurring between 2% and 10% of the varieties in the collection were classified as rare alleles (Alvarez et al 2007). In this study, 85 frequent alleles were identified at 34 microsatellite loci, with an average of 2.50 alleles per locus.…”
Section: Frequent Rare and Unique Allelesmentioning
confidence: 86%
“…The use of these molecular markers investigates the genotypic variations among the different rice geno types are previously reported by some researchers [13,[24][25][26][27][28]. The implication of these molecular tech niques to investigate the genetics of Pakistani basmati genotypes is much limited.…”
Section: Discussionmentioning
confidence: 99%